Influence of various treatments on pre and post germination properties of Callistephus chinensis (L.) Nees cv. Powderpuff - Wani, Muneeb Ahmad; Khan, FU; Nazki, Imityaz Tahir; Din, Ambreena; Iqbal, Shameen; Qadri, ZA (Bangladesh Journal of Botany, 2019)
Seeds of China aster cv. Powderpuff were subjected to two conditioning techniques viz, hydroconditioning and halo-conditioning at different levels of concentrations and subjected time durations, constituting a total of 16 treatment combinations (P1 - P15) along with control (P0). Hydro-priming for 12 hrs and the halo-priming with 2 % KNO3 for 12 hrs significantly improved germination, mean germination time, germination index, germination rate index and growth attributes of China aster cv. Powderpuff. Hydropriming being simple economical and eco/subject friendly and safe is recommended for effective germination and growth of China aster cv. Powderpuff.